DUKUNGAN KURIKULUM 2004 TERHADAP PEMBELAJARAN PENGETAHUAN ALAM TERINTEGRASI DI SMP - Bambang Subali, Slamet Suyanto, Paidi & Heru Kuswanto (LPMPP Universitas Negeri Yogyakarta, 2005)
AbstractThe new curriculum for junior high schools known as Curriculum 2004 calls for a change in the name of the school subject PhysicalScience into Physical Knowledge. The change in name has veryimportant consquences on education in science. One of the mostimportant consquences is that the subject should be taught in anintegrated way. This article studies the consquences of the changein the name of the subject on its instruction and whether thestructure of the curriculum enables the subject to be taught in an integratedway.The results of the study indicate that a consquence of the change in the name of the subject is that the way junior high school students learn science is not to be as scientific as scientists; rather, they are to come only to the level of introduction to concepts and scientific work which is applied in nature (which implies applied science). Therefore, there needs to be a change in the formulation of leaning objectives and a simplification of the basic copmpetencies to be achieved and the indicators of achievement. An integrated teaching of the subject in an integrated way, however, can ideally be conducted only when the development of the important aspects (or the strands) of the subject in the curriculum is based on themes or problems instead of objects. The objects selected should represent a facilitation of the mastery of scientific concepts to be developed in students, as seen in the structure of the curriculum used in Singapore or of the one proposed a science teachers association in the United States.Key words: science education curriculum, integrated science education